2009
DOI: 10.1007/s10342-009-0303-5
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical differences in N-dynamics between Luxembourg soils: litter quality or parent material?

Abstract: To explore whether litter quality could alter differences in N-dynamics between soil types, we compared spruce and beech growing on soils with parent material sandstone and limestone, and beech and hornbeam on acid marl and limestone. We measured pH, organic matter content, C:N ratio, soil respiration and net N-mineralization of the organic layer and the mineral topsoil in a laboratory incubation experiment and estimated gross N-mineralization and immobilization with a simulation model. Species effects were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
(103 reference statements)
0
6
1
Order By: Relevance
“…This remarkable variation in the effects of species, genera, and plant functional types on net N min rates probably arises, in part, because the effect of plant traits on net N min depends on environmental factors and stand properties. For example, rankings for net N min rates among tree species can depend on stand age (Pare´and Bergeron 1996), soil horizon (Thomas and Prescott 2000), and soil type (Ste-Marie et al 2007, Kooijman andSmit 2009). The relative effects of different plant traits on net N min rates also are likely to depend on these and other factors.…”
Section: Discussionmentioning
confidence: 99%
“…This remarkable variation in the effects of species, genera, and plant functional types on net N min rates probably arises, in part, because the effect of plant traits on net N min depends on environmental factors and stand properties. For example, rankings for net N min rates among tree species can depend on stand age (Pare´and Bergeron 1996), soil horizon (Thomas and Prescott 2000), and soil type (Ste-Marie et al 2007, Kooijman andSmit 2009). The relative effects of different plant traits on net N min rates also are likely to depend on these and other factors.…”
Section: Discussionmentioning
confidence: 99%
“…In the control treatment, the results further support the hypothesis that neutral soils have higher biological activity than acidic soils, but that net N-mineralization may nevertheless be lower due to higher microbial N-demand and immobilization. This could explain why net N-mineralization was lower in neutral than in acid soil in e.g., Zöttle (1960), Davy and Taylor (1974), Verhoeven et al (1990), Kooijman and Besse (2002), Kooijman et al (2008), Kooijman and Smit (2009) and Mettrop et al (2014).…”
Section: Different Roles Of Bacteria and Fungimentioning
confidence: 99%
“…Respiration was measured at the start and end of the incubation experiments, as preliminary experiments indicated that CO 2production during the experiment was more or less constant (Kooijman and Smit, 2009). Fresh or incubated material was placed in open glass jars during one night, with the equivalent of 5 g dry weight for organic and 10-15 g for mineral samples.…”
Section: Laboratory Incubation Experimentsmentioning
confidence: 99%
See 2 more Smart Citations